Abundance of Phytoplankton and Primary Productivity Levels in the Waters of Kasiak Island West Sumatera Province - Silaban, Santi Maria; Thamrin, Thamrin; Siregar, Sofyan Husein (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2022)
This study was conducted in June 2021. Data collection of phytoplankton abundance and primary productivity was carried out in the waters of Kasiak Island of West Sumatra Province. The aim of the study was to analyze phytoplankton abundance, primary productivity vertically, and the effect of phytoplankton abundance on primary productivity in the waters of Kasiak Island. Based on the results of this study obtained that the abundance of phytoplankton on the surface (0 m) ranges from 41.67-187.50 ind/L. The abundance of phytoplankton in the depth of 5 ranges from 20.83-104.17 ind/L. While the primary productivity level of the results of the measurement of dissolved oxygen of the surface (0 meters) is obtained ranging from 7.6-11.2 mg/L while at a depth (5 m) range from 8-10.4 mg/L. Based on simple linear regression analysis on the surface (0) obtained the equation Y = 42.26x + 0.48x. The value of r2 = 0.2031 while the correlation coefficient value (r) is 0.4507. Based on the results of a simple linear regression analysis it is stated that the increasing abundance of phytoplankton the primary productivity level of the waters increases. As for the depth of 5 meters the equation Y = 46.45x + 0.07x. The value of r2 = 0.0183 while the correlation coefficient value (r) is 0.1335. Based on linear regression obtained a negative correlation means that reducing the abundance of phytoplankton will reduce the productivity of the waters